SHARING BUDIDAYA DAUN BAWANG DAN GERAKAN TANAM BERSAMA DI KAMPUNG WALELAGAMA - Buni, Novi Laka; Wulandari, Futri (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
The activity of sharing onion gardening and collective planting in Walelagama Village, Jayawijaya Regency, is an initiative aimed at enhancing food security and empowering the local community. This event aims to enhance residents' knowledge and skills in cultivating onions effectively and sustainably, while also encouraging active participation in collective planting efforts. Through training, demonstrations of best practices, and community collaboration, it is hoped that a broader culture of planting will be established and agricultural productivity in the area will increase. This activity also supports efforts to conserve natural resources and improve the welfare of the local community. The results of this activity show increased interest and capability among residents in onion cultivation, as well as the creation of community solidarity in maintaining sustainable agriculture in Walelagama Village.